2012
DOI: 10.1007/s00221-012-3059-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of oddball detection in self-motion heading: A high-density event-related potential study of vestibular integration

Abstract: The perception of self-motion is a product of the integration of information from both visual and non-visual cues, to which the vestibular system is a central contributor. It is well documented that vestibular dysfunction leads to impaired movement and balance, dizziness and falls, and yet our knowledge of the neuronal processing of vestibular signals remains relatively sparse. In this study, high-density electroencephalographic recordings were deployed to investigate the neural processes associated with vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Previous studies showed that the motion and vestibular stimuli elicited an evoked potential over the fronto-central areas such as Fz, Cz, and Pz (Elidan et al, 1991;Loose et al, 1999;Nolan et al, 2012;Probst et al, 1997;Rodionov et al, 1996). The cortical regions involve in the processing of motion/vestibular cues include the posterior parietal cortex, insular, frontal cortex,…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Previous studies showed that the motion and vestibular stimuli elicited an evoked potential over the fronto-central areas such as Fz, Cz, and Pz (Elidan et al, 1991;Loose et al, 1999;Nolan et al, 2012;Probst et al, 1997;Rodionov et al, 1996). The cortical regions involve in the processing of motion/vestibular cues include the posterior parietal cortex, insular, frontal cortex,…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The centroparietal P300 (alternatively labelled ‘P3’ or ‘P3b’) is a large‐amplitude positive event‐related potential (ERP) component which peaks at ~ 300–600 ms following the presentation of any task‐relevant stimulus, regardless of its sensory modality (Nieuwenhuis et al ., ; Polich & Criado, ; Nolan et al ., ). This component has drawn relentless interest since its initial discovery in 1965 (Sutton et al ., ) due to its apparent relevance to a wide variety of cognitive operations and its disruption in a number of prominent brain disorders (Polich et al ., ; Santosh et al ., ; Mavrogiorgou et al ., ; Prox et al ., ; Verleger et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Our group (De Sanctis, Butler, Green, Snyder, & Foxe, 2012; De Sanctis et al, 2014; Nolan et al, 2012; Nolan, Whelan, Reilly, Bulthoff, & Butler, 2009) and others (Castermans & Duvinage, 2013; Castermans, Duvinage, Cheron, & Dutoit, 2014; De Vos, Gandras, & Debener, 2014; Debener, Minow, Emkes, Gandras, & de Vos, 2012; Duvinage et al, 2012; Gramann, Ferris, et al, 2014; Gramann, Gwin, Bigdely-Shamlo, Ferris, & Makeig, 2010; Hoellinger et al, 2013; Reis et al, 2014) have shown that it is entirely feasible to record robust event-related potentials (ERPs) from a cognitive task while participants are in motion, without a significant difference in signal-to-noise ratio compared to stationary conditions. The MoBI approach integrates high-density electro-cortical activity with simultaneously acquired body tracking data to investigate brain activity and gait pattern as participants walk on a treadmill while also performing a cognitive task.…”
Section: Introductionmentioning
confidence: 99%